Diferentes substratos e tipos de estacas no enraizamento de Ixora coccinea L. ‘Compacta’ - Cardoso, Alcione Serrão (Brasil, 2022)
Ixora coccinea L. ‘Compacta’ is one of the most used ornamental shrub species in the composition of landscape projects, due to the beauty of its leaves and flowers and the different types of plant arrangements used in gardens, such as ornamental massif, hedge and border. The objective of this study was to identify the most suitable type of stem cutting for I. coccinea rooting and the most favorable substrate for rooting and initial growth of seedlings. The experiment was conducted in the open air and the raw material used in the composition of the substrates was: earth, sand tanned bovine manure. The experimental design used was in randomized blocks, in a 2x8 factorial arrangement, with two types of cuttings (apical and intermediate, in which all cuttings were prepared 24 cm long) and eight different substrates: S1 – earth; S2 – sand; S3 – earth + sand in proportion 1:1; S4 – earth + sand 2:1; S5 – earth + sand 1:2; S6 – earth + manure 1:1; S7 – sand + manure 1:1 and S8 – earth + sand + manure 1:1:1, with four repetitions of eight stakes, each experimental unit. The evaluation of the experiment was carried out at 100 days after planting the cuttings. The characteristics evaluated were: number of shoots per cutting, percentage of sprouted cuttings (%), percentage of rooted cuttings (%), number of roots, volume of roots (cm3) and dry matter of roots (g). The collected data were 8 submitted to analysis of variance, using the F test (p>0.05) and the means compared by the Scott-knott test at 5% probability. Apical cuttings planted in earth (S1), earth + sand (S3, S4 and S5) and earth + sand + manure (S8) substrate had significant increases in rooting. The substrate earth provided greater initial growth of the seedlings.